2017
DOI: 10.1002/adma.201701220
|View full text |Cite
|
Sign up to set email alerts
|

Ink‐Free Reversible Optical Writing in Monolayers by Polymerization of a Trifunctional Monomer: Toward Rewritable “Molecular Paper”

Abstract: A Langmuir-Blodgett film consisting of a dense array of trifunctional monomers bearing three 1,8-diazaanthracene units is polymerized at an air/water interface or after transfer on solid substrates. The transfer does not affect the excimer fluorescence of the film, indicating that the monomers' packing with their diazaanthracene units stacked face-to-face is retained-a prerequisite for successful polymerization. The monomer film can be polymerized in confined areas on solid substrates by UV irradiation with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
0
29
0
2
Order By: Relevance
“…To date,s everal different monomers have been used in interfacial polymerizations ( Figure 3). Monomers 1-4 are classical amphiphiles [56,57,66] and all other monomers except for 5 [67] have moieties capable of forming hydrogen bonds to the subphase. These moieties are the nitrogen atoms of the heteroaromatics in 6-9, [54,55,68] the thiol groups in 10 and 11, [25,26,69] and the aldehyde and aromatic amine groups in 12/13 and 14/15.…”
Section: Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date,s everal different monomers have been used in interfacial polymerizations ( Figure 3). Monomers 1-4 are classical amphiphiles [56,57,66] and all other monomers except for 5 [67] have moieties capable of forming hydrogen bonds to the subphase. These moieties are the nitrogen atoms of the heteroaromatics in 6-9, [54,55,68] the thiol groups in 10 and 11, [25,26,69] and the aldehyde and aromatic amine groups in 12/13 and 14/15.…”
Section: Reviewsmentioning
confidence: 99%
“…[12] 2D polymers may also be integrated into optical devices as novel, ultrathin photo-sensitive materials for integrated optical memories and recording components. [96] Some monolayer sheets,f or example that from monomer 3, [66] exhibit extreme thinness and macroscopic lateral size with reversible writability.T his could allow for implementation of such sensitive layers with other planar miniature optical components such as meta-lenses and waveguides. [97] By contrast to the single-crystal approach, where the finer structural details can be clarified by Bragg and diffuse XRD patterns, [98] the structures obtained at air-water and liquid-liquid interfaces are more challenging to identify.Asaresult, it may be tempting to give up too early on the analysis of the sheets obtained at an interface and to place too much emphasis on structure models than real structures when entering into application oriented studies.Although for some applications it may not matter whether as heet has high crystallinity or large domain sizes,for other applications,such as electronics,e nergy storage,m echanics,m embranes,i tw ill be essential.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Thei nvisibility of the letters on paper under visible light reminds us that the paper coated with polycrystals of 1 can be applied as rewritable PL paper.T od ate,r esearch on rewritable paper was mainly focused on the mechanochromism, [16] solvatochromism, [17] and photochromism, [18] and so on, [19] while the application of PL materials in rewritable PL paper was seldom reported. Owing to the competition between kinetic and thermodynamic crystallization processes during the cooling process of the molten of 1,h eating the designated area on the paper above T m1 would melt the polycrystals,a nd IL@2 with red emission would be formed after natural cooling the molten to RT.T he written contents can hardly be photocopied, which provides the opportunity for high-level anti-counterfeiting technology.T .A ida et al firstly reported the Cu I pyrazolate complexes with thermally tunable dichroic emission and their application in thermally rewritable phosphorescent paper as next-generation security technology.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[176] Bei STM-basierten Analysen ist besonders zu beachten, dass die Polymere eventuell nicht direkt auf dem Substrat liegen. [143] Damit eignen sich diese extrem dünnen, aber lateral makroskopisch ausgedehnten Schichten prinzipiell als optische Datenträger [180][181][182][183] z. Beides ist nur mit großer Sorgfalt mçglich, aber insbesondere unter Verwendung der zweiten Methode ließen sich wichtige Information gewinnen, da so auch durch konformative Optimierung verborgene Netzwerkstrukturen zum Vorschein kommen kçnnten.…”
Section: Ausblickunclassified
“…Monolagen des Monomers 3 zum Beispiel lassen sich unter Polymerisation der belichteten Areale reversibel beschreiben. [143] Damit eignen sich diese extrem dünnen, aber lateral makroskopisch ausgedehnten Schichten prinzipiell als optische Datenträger [180][181][182][183] z. B. in Verbindung mit anderen dünnen optischen Komponenten wie Metalinsen oder Lichtleitern.…”
unclassified